Preparation of carbon nanotubes/TiO2-polyvinylidene fluoride nanocomposites and composite films. Issue 1 (1st April 2022) - Hui, Yang; Jiaqi, Zhang; Huan, He
Abstract: In this paper, PVDF membrane was discussed, many modified materials were found from the shortage of materials, and finally carbon nanotubes/TiO2 hybrid materials were synthesized. The preparation methods and synthesis conditions of carbon nanotubes/TiO2 -polyvinylidene fluoride nano composite ultrafiltration membrane were studied, and the advanced membrane treatment technology was prospected. Secondly, multi-walled carbon nanotubes/Ti02 hybrid materials were synthesized by hydrothermal method and sol-gel method.